Role of non-governmental organizations in moving toward universal health coverage: A case study in Iran - Arman Sanadgol; Arman Sanadgol; Leila Doshmangir; Leila Doshmangir; Rahim Khodayari-Zarnaq; Vladimir Sergeevich Gordeev; Vladimir Sergeevich Gordeev (Frontiers in Public Health, 2022)
BackgroundDelivering essential health services through non-governmental organizations (NGOs) could facilitate moving toward universal health coverage (UHC), especially in low- and middle-income countries. This study investigates the viewpoints of Iranian health system experts and executive stakeholders on the role of NGOs in moving toward UHC.MethodWe conducted 33 semi-structured interviews with health policymakers, NGO representatives at the national and provincial level, and other key informants and analyzed using content analyses methods, using MAXQDA 12. The inductive-deductive approach was used for qualitative data analyses.ResultBased on the thematic analysis of interviews and document reviews, nine main themes and one hundred and five sub-themes were identified. Each theme was categorized based on NGO-, society-, and government-related factors.ConclusionRecognizing the critical role of NGOs and their contribution in moving toward UHC is essential, particularly in the local context. Collaboration between NGO stakeholders and the government could facilitate moving toward UHC.